(3GdSQ aj CfaGS GdUhajIs - (3GdLfjO Hf eMeO Hf GdLfjO GdHZOGOj GdNRGR, CHh GdbGSe , J (B297 (3g` s
(3ChdgG (B:s
(3jHOC HHGH UaI GdCfaGS s
(3BNQgG (B:s
(3Hef GdYRjeI ai eMh OhGYi GdLQjeI Je GdcJGH hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JUha (B287) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs